Development of The Android Application Suka EduPAI as An Interactive Learning Media for Islamic Religious Education - Ikhsan Rifai; Anggita Dewi Apriliana; Asniyah Nailasariy; Adhi Setiyawan (PAEDAGOGIA, 2024)
Lack of interactivity inside and outside the classroom can be a problem in learning. Android apps can help increase the level of interactivity among students, teachers and subject matter. Preliminary studies show that PAI teachers need Android applications to support the learning process in class and outside the classroom. This research aims to develop interactive learning media Suka EduPAI for Islamic Religious Education on Umayyad in Andalusia material. The population was taken from all class VII of SMP Negeri 2 Sewon with a sample of Class VII H. The research method used the APPED model (Analysis, Design, Production, Evaluation and Dissemination). Data collected from ongoing evaluation, and alpha testing from media experts, material experts and instructional experts shows that the application is valid and suitable for use. The assessment for this media from the material expert gets a high category of assessment of 73.3%, the media expert assessment gets a very high category of 88%, the instructional expert assessment gets a very high category with a score of 90%, and the student response gets a very high satisfaction with a score of 94%. Thus  the Suka EduPAI application is feasible and can be implemented in a classroom setting.